ANALISIS PELAKSANAAN KEBIJAKAN PEMBUATAN SUMUR RESAPAN DI KECAMATAN TAMPAN KOTA PEKANBARU - Fhatma Rizha; Zulkifli Zulkifli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This study took place at the Department of Tata Ruang dan Bangunan Pekanbaru City and districts of Tampan. The issues in this study was found in the formulation of the problem, namely how to exercise policy-making infiltration wells in the district Tampan Pekanbaru city and the factors inhibiting implementation of the policy-making infiltration wells. This study aims to determine implementation Policy Making Infiltration Wells in District implementation Pekanbaru city as well as factors that hinder the implementation of development policy-making Infiltration Wells in District Tampan Pekanbaru. This study uses descriptive survey with reference to the concept of the theory of Van Meter and Van Horn consist of Standards and policy targets, Resources, Communications and strengthening inter-organizational activities, characteristics executive department, economic conditions, political and social, Disposition executor. In collecting the data, the authors use the technique of questionnaires, interviews, observation and documentation. Based on the results of research and discussion can be seen that the implementation of the policy-making infiltration wells in the district Tampan Pekanbaru city when seen from the respondents' answers employee has been accomplished while the results of the Community answer Handsome districts is quite accomplished.